Priming an approach motivational state to enhance intergroup contact intention - Lam, Jerlyn (Nanyang Technological University, 2020)
This study seeks to explore the influence of approach and avoidance motivational states on intentions to engage in contact with an outgroup member. The contact hypothesis posits that contact between members of two groups improves intergroup relations, yet recent naturalistic research reveals that people do not naturally initiate contact with the outgroup. As such, the purpose of this paper is to identify factors that would increase intentions to seek intergroup contact. I hypothesize that priming of an approach (versus avoidance) motivational state will increase outgroup contact intentions, and that this relationship is mediated by an increased focus in benefits (versus costs) of intergroup contact. In this study, 83 participants were randomly assigned to two conditions and primed with either an approach or avoidance motivational state. They then completed a questionnaire measuring their cost-benefit analyses, ingroup and outgroup contact intentions, motivational state, and familiarity of outgroups. Results revealed that after controlling for ingroup contact intention and familiarity of the outgroup, motivational states were not associated with outgroup contact intention, nor with focus on benefits (versus costs) of intergroup contact. However, this focus on benefits (versus costs) of intergroup contact was associated with outgroup contact intention, even after controlling for ingroup contact intention and familiarity of the outgroup. Theoretical and practical implications of the results, as well as limitations of the study and ideas for future research are discussed.